2020
DOI: 10.1002/adma.202003263
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[n]arene‐Based Supramolecular Switches in Solution and on Surfaces

Abstract: response to specific physical or chemical stimuli including, but not limited to, pH, light, redox, competitive agents, and tem perature. In particular, pseudorotaxanes, comprising of a rod component without bulky end groups encircled by a wheel entity via noncovalent bonds, can be employed as a superior class of candidates for supramolecular switches. [3] There fore, the study of macrocyclic receptors as the wheel entity of pseudorotaxanes has become one of the research hotspots in the field and received great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 98 publications
0
58
0
Order By: Relevance
“…The water-soluble amino pillar[5]arene functional with Au nanoparticles serves as a fluorescence probe for dopamine determination [ 100 ]. The pillar[n]arene macromolecule shows stable HG supramolecular switches in solution and on surfaces due to their binding ability of various guest molecules and multipurpose, adaptable functionalization [ 101 ]. The photo-responsive composite surface was assembled via adjusting azobenzene-calix[4]arene on a micro-structured silicon substrate using UV light irradiation as a stimulus [ 102 ].…”
Section: Stimuli-responsive Hg Systemsmentioning
confidence: 99%
“…The water-soluble amino pillar[5]arene functional with Au nanoparticles serves as a fluorescence probe for dopamine determination [ 100 ]. The pillar[n]arene macromolecule shows stable HG supramolecular switches in solution and on surfaces due to their binding ability of various guest molecules and multipurpose, adaptable functionalization [ 101 ]. The photo-responsive composite surface was assembled via adjusting azobenzene-calix[4]arene on a micro-structured silicon substrate using UV light irradiation as a stimulus [ 102 ].…”
Section: Stimuli-responsive Hg Systemsmentioning
confidence: 99%
“…Compared with molecular chirality, the supramolecular chirality is more attractive in terms of their regulatability by the external conditions such as temperature ( Yao et al, 2017 ; Fan et al, 2019 ), pH ( Kanagaraj et al, 2020 ; Liang et al, 2020 ; Hao et al, 2021 ), redox ( Xiao et al, 2020 ), light ( De Poli et al, 2016 ), chemical additives ( Lee et al, 2018 ), pressure ( Yao et al, 2021a ), and solvents ( Borovkov et al, 2003b ; Fan et al, 2019 ). Pillar[n]arenes ( Ogoshi et al, 2008 ; Xue et al, 2012 ; Pan et al, 2015 ; Fan et al, 2016 ; Jie et al, 2018 ; Lv et al, 2018 ; Li G. et al, 2019 ; Xiao et al, 2019 ; Ji et al, 2020a ; Lou and Yang, 2020 ; Mi et al, 2020 ; Liu et al, 2021 ; Peng et al, 2021 ), as a relatively new class of synthetic macrocyclic hosts with some unique properties ( Guo et al, (2018) ; Lai et al, (2019) ; Liu et al, (2019) ; Wang et al, (2021 ), have proved to be an ideal platform to construct unimolecular chirality based on different external stimuli-driven. We have demonstrated that the chirality of pillar[n]arene derivatives could be manipulated by external stimuli, including temperature, redox, light, and pressure ( Yao et al, 2017 ; Xiao et al, 2020 ; Yao et al, 2021a ; Yao et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Macrocycles have made wide application in many fields, such as ion channels, sensing, molecule adsorption, catalysis, and cancer treatment. [31][32][33][34][35][36][37][38][39][40] In our previous work, macrocyclic pillar [6]arene was first developed as photoinitiators and successfully used for initiating polymerization under the irradiation of mercury lamp light (295 nm). [41] Prismarene is a novel kind of macrocycle whose 2,6-dimethoxynaphthalene units are connected by methylene bridges, which was first synthesized in 2020.…”
Section: Introductionmentioning
confidence: 99%